Microalgal Biodiesel Production: Realizing the Sustainability Index - Patnaik, Reeza; Mallick, Nirupama (Frontiers in Bioengineering and Biotechnology, 2021)
Search for new and renewable sources of energy has made research reach the tiny little tots, microalgae for the production of biodiesel. But despite years of research on the topic, a definitive statement, declaring microalgae as an economically, environmentally, and socially sustainable resource is yet to be seen or heard of. With technological and scientific glitches being blamed for this delay in the progress of the production system, an assessment of the sustainability indices achieved so far by the microalgal biodiesel is important to be done so as to direct future research efforts in a more coordinated manner to achieve the sustainability mark. This article provides a review of the current economic, environmental, and social status of microalgal biodiesel and the strategies adopted to achieve them, with suggestions to address the challenges faced by the microalgal biodiesel production system.